2008
DOI: 10.1109/tbme.2007.900562
|View full text |Cite
|
Sign up to set email alerts
|

Critical Analysis of the Impact of Glottal Features in the Classification of Clinical Depression in Speech

Abstract: The motivation for this work is in an attempt to rectify the current lack of objective tools for clinical analysis of emotional disorders. This study involves the examination of a large breadth of objectively measurable features for use in discriminating depressed speech. Analysis is based on features related to prosodics, the vocal tract, and parameters extracted directly from the glottal waveform. Discrimination of the depressed speech was based on a feature selection strategy utilizing the following combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
119
1
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(127 citation statements)
references
References 39 publications
4
119
1
3
Order By: Relevance
“…Since the durations differ for each subject, which may affect the comparison results, we only used an equal amount of speech data from each subject (92s) in this paper. We acknowledge that the amount of data used here is relatively small, but this is a common problem [5,14] in similar studies. As we continue to collect more data, future studies will be able to report on a larger dataset.…”
Section: Real-world Clinically Validated Datamentioning
confidence: 98%
See 1 more Smart Citation
“…Since the durations differ for each subject, which may affect the comparison results, we only used an equal amount of speech data from each subject (92s) in this paper. We acknowledge that the amount of data used here is relatively small, but this is a common problem [5,14] in similar studies. As we continue to collect more data, future studies will be able to report on a larger dataset.…”
Section: Real-world Clinically Validated Datamentioning
confidence: 98%
“…Moreover, the research found that formants are a feature significantly distinguishing depressed from non-depressed speech [4,5], with a noticeable decrease in the second formant for depressed compared to healthy controls [4]. There is convincing evidence that sadness and depression are associated with a decrease in loudness and energy [6].…”
Section: Related Workmentioning
confidence: 99%
“…Un locutor muestra estrés en su habla de diferente forma cuando produce una aseveración que concuerda con su punto de vista real que en el caso de tener que elaborar un discurso ficticio para parecer creíble cuando expresa una opinión contraria a su punto de vista. Este estrés se manifiesta en su calidad de fonación [125].…”
Section: Donación De La Vozunclassified
“…Otras aproximaciones consideran la vibración de las cuerdas vocales incluyendo los parámetros del ciclo glotal [90], [124], como la fase de duración de la apertura y cierre de las cuerdas vocales, los ratios entre la fase de apertura y cierre del ciclo glotal completo, el jitter glotal y el shimmer glotal [125], [196].…”
Section: Aspectos Generalesunclassified
See 1 more Smart Citation